Evolution of contrast agents for ultrasound imaging and ultrasound-mediated drug delivery - Paefgen, Vera; Doleschel, Dennis; Kiessling, Fabian (Frontiers in Pharmacology, 2015)
Ultrasound is one of the most frequently used diagnostic methods. It is a non-invasive, comparably inexpensive imaging method with a broad spectrum of applications, which can be increased even more by using bubbles as contrast agents. There are various different types of bubbles: filled with different gases, composed of soft- or hard-shell materials, and ranging in size from nano- to micrometers. These intravascular contrast agents enable functional analyses, e.g. to acquire organ perfusion in real-time. Molecular analyses are achieved by coupling specific ligands to the bubbles’ shell, which bind to marker molecules in the area of interest. Bubbles can also be loaded with or attached to drugs, peptides or genes and can be destroyed by ultrasound pulses to locally release the entrapped agent. Recent studies show that ultrasound contrast agents are also valuable tools in hyperthermia-induced ablation therapy of tumors, or can increase cellular uptake of locally released drugs by enhancing membrane permeability. This review summarizes important steps in the development of ultrasound contrast agents and introduces the current clinical applications of contrast-enhanced ultrasound. Additionally, an overview of the recent developments in ultrasound probe design for functional and molecular diagnosis as well as for drug delivery is given.